(untitled) (Research, Society and Development, 2021)
Mandibular fractures after third molar extraction are low incidence events, but they can occur due to a smaller amount of bone tissue in the mandibular angle region due to the presence of the tooth. And this may also be accompanied by secondary complications and which must be treated correctly. Thus, the aim of this article is to carry out a clinical case report of a patient who developed an incomplete mandibular angle fracture after third molar extraction and with inferior alveolar nerve paresthesia and infection, which were treated with the application of photodynamic therapy antimicrobial (aPDT). A 33-year-old patient came to the hospital complaining of severe trismus after extraction of tooth 38. On physical examination, it was possible to observe edema in the left mandibular angle region and active purulent drainage in the 38-year-old region. On computed tomography it was possible to observe an incomplete fracture in the left mandibular angle region, affecting both buccal and lingual cortical bone. Drug therapy for the treatment of infection was associated with aPDT therapy until remission of signs of infection and photobiomodulator therapy for the treatment of inferior alveolar nerve paresthesia, with periodic panoramic radiographs being performed. After 4 months, it was possible to observe a complete remission of the infection and paresthesia, in addition to consolidation of the bone corticals that had been fractured. Thus, it is possible to conclude that aPDT therapy can be used as an alternative for the conservative treatment of incomplete mandible fractures after third molar extraction, as well as secondary complications.